Handbook of Polymer Nanocomposites. Processing, Performance and ApplicationL: Volume C: Polymer Nanocomposites of Cellulose Nanoparticles - Pandey, J.K (Springer, 2015)
Volume C forms one volume of a Handbook about Polymer Nanocomposites. Volume C deals with Polymer nano-composites of cellulose nano-particles. The preparation, architecture, characterisation, properties and application of polymer nanocomposites are discussed within some 27 chapters. Each chapter has been authored by experts in the respective field.